2021
DOI: 10.1037/int0000252
|View full text |Cite
|
Sign up to set email alerts
|

Applying emotion-focused therapy to work with the “anorexic voice” within anorexia nervosa: A brief intervention.

Abstract: Existent treatments for anorexia nervosa (AN) have produced dissatisfactory outcomes.Research suggests that many people with AN experience an internal 'voice' which is related to eating disorder symptoms and relapse. This study was designed to consider the feasibility and acceptability of a new emotion-focused treatment of AN, which is designed to work directly with the anorexic voice (AV) ('EFT-AV'). Six adult clients diagnosed with AN who were experiencing an AV and awaiting psychological treatment were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
(132 reference statements)
0
10
0
Order By: Relevance
“…Accordingly, changing the ways individuals relate, respond to, and understand the EDV may support recovery and prevent relapse (Jenkins & Ogden, 2012; Tierney & Fox, 2010). Given that studies examining EDV interventions have reported promising outcomes (e.g., Dolhanty & Greenberg, 2007; Hibbs et al, in press; Mountford & Waller, 2006), developing voice‐related interventions may be an important direction for working with individuals with eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, changing the ways individuals relate, respond to, and understand the EDV may support recovery and prevent relapse (Jenkins & Ogden, 2012; Tierney & Fox, 2010). Given that studies examining EDV interventions have reported promising outcomes (e.g., Dolhanty & Greenberg, 2007; Hibbs et al, in press; Mountford & Waller, 2006), developing voice‐related interventions may be an important direction for working with individuals with eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…All 11 studies examined clients' experiences of helpful aspects of EFT, while seven studies featured difficult but helpful aspects of EFT (Angus & Kagan, 2013; Elliott, 2013; Hibbs et al, 2020; Nødtvedt et al, 2019/ Stiegler et al, 2018/Stige et al, 2021; O'Connell Kent et al, 2020; Steinmann et al, 2017; Timulak et al, 2017), and six studies featured experiences of unhelpful aspects of EFT (Hibbs et al, 2020; MacLeod et al, 2012; Nødtvedt et al, 2019; O'Connell Kent et al, 2020; Steinmann et al, 2017; Stiegler et al, 2018; Stige et al, 2021; Timulak et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This meta‐category differs from the previous meta‐category in that it covers experiences that do not refer explicitly to the experiential techniques/nature of EFT. One client reported “I found it useful because it kind of gave you a way… of boxing up thoughts and feelings and starting to untangle some, yeah, the untangling process” (Hibbs et al, 2020, p. 14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations